Systematization of Information Management in Sea Turtle Recovery - Andrade Colombani, Sergio David (2024)
Sea turtles have faced the impacts of human activities for many decades, and their current threats are so severe that they are critically endangered. One of the most significant threats to their populations is entanglement in fishing gear. To protect and recover these animals, an advanced information collection system has been developed. This system allows fishermen to record the GPS location, date, and time when a turtle becomes trapped in their fishing nets. This crucial information is collected by the ”Quelona” Sea Turtle Rescue Center, providing valuable data for research and conservation efforts. The project was designed with simplicity in mind, ensuring that it is easy to use. It also addresses challenges such as poor telephone service coverage and data redundancy, ensuring that the system remains functional in difficult conditions. By addressing these issues, the project aims to significantly contribute to the preservation and recovery of sea turtle populations.